Factors Affecting Health Care Provider Knowledge and Acceptance of Biosimilar Medicines: A Systematic Review - Leonard, Emily; Wascovich, Michael; Oskouei, Sonia; Gurz, Paula; Carpenter, Delesha (Journal of managed care & specialty pharmacy, 2019)
Newly developed biosimilar agents confer significant cost-saving advantages, yielding the potential to mitigate rising drug costs and expand patient access to care for important biologic therapies. Biosimilar market uptake greatly depends on health care provider willingness to promote, prescribe, and use biosimilars in clinical practice. To perform a systematic review evaluating current U.S. and European health care provider knowledge, perceptions, and prescribing behaviors of biosimilar medicines to assess the need for clinician-directed biosimilar education. An electronic literature search was conducted using journal databases, including PubMed, Embase, and Cochrane Library. Terms related to biosimilar agents, survey questionnaires, and education were used. Two independent reviewers evaluated 158 citations published from January 1, 2014, to March 5, 2018 that were the result of this search. Studies in English were included if they surveyed U.S. or European physician and/or pharmacist knowledge, attitudes, and/or prescribing preferences of biosimilar drugs. Overall trends in prescribing behavior and perceptions were abstracted. A total of 20 studies met inclusion criteria. Three studies originated from the United States and 17 were from Europe. Hospital specialists, gastroenterologists, and rheumatologists were the most frequently surveyed practitioners. The percentage of biosimilar prescribing varied widely between countries and within similar practice fields. If used, biosimilars were predominantly prescribed in biologic treatment-naive patients. An overall lack of biosimilar familiarity in U.S. and European health care settings accompanied concerns about biosimilar safety, efficacy, extrapolation, and interchangeability. Detailed descriptions of biosimilar education programs were lacking within the literature. Findings from this review indicate that U.S. and European health care providers still approach biosimilar medicines with caution, citing limited biosimilar knowledge, low prescribing comfort, and safety and efficacy concerns as main deterrents for biosimilar use. To realize the full cost-saving potential of biosimilar medicines, clinician-directed biosimilar education will be imperative to address gaps in biosimilar knowledge, facilitate prescribing changes, and ultimately increase biosimilar use. No outside funding supported this study. The authors have nothing to disclose.